RETRACTED: Cardiovascular and mortality outcomes of DPP-4 inhibitors vs. sulfonylureas as metformin add-on therapy in patients with type 2 diabetes: A systematic review and meta-analysis - Refli Hasan; Uliana Y. Chugaeva; Mahdi Mohammadian; Somayeh Zamanifard; Abdollah Mohammadian-Hafshejani (PLoS ONE, 2025)
Background Type 2 diabetes significantly increase the risk of cardiovascular disease and mortality. This systematic review and meta-analysis compared cardiovascular and mortality outcomes in type 2 diabetes patients receiving dipeptidyl peptidase-4 inhibitors (DPP-4is) plus metformin versus sulfonylureas (SUs) plus metformin as add-on therapy. Methods PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, Google Scholar, and Scopus were searched through January 1, 2025, for studies comparing DPP-4is plus metformin versus SUs plus metformin in type 2 diabetes patients. Outcomes of interest were major adverse cardiovascular events and all-cause mortality. Heterogeneity was assessed using Cochran’s Q test and I 2 statistic. Publication bias was evaluated with Begg’s and Egger’s tests. Study quality was assessed with the Jadad scale (for randomized controlled trials) and the Newcastle-Ottawa Scale (for observational studies). Results Twenty-seven studies (2012–2024), encompassing 1,505,821 participants, were included in the analysis. Major adverse cardiovascular events were reported in 21 studies, and all-cause mortality data were available from 19 studies. Meta-analysis revealed a significantly lower risk of both major adverse cardiovascular events (risk ratio [RR]: 0.79; 95% confidence interval [CI]: 0.73–0.84; p < 0.001) and all-cause mortality (RR: 0.79; 95% CI: 0.71–0.88; p < 0.001) in patients with diabetes treated with DPP-4 inhibitors plus metformin compared to those treated with SUs plus metformin. No publication bias was detected. Conclusion In type 2 diabetes patients treated with metformin, adding a DPP-4is is associated with significantly lower risks of major adverse cardiovascular events and all-cause mortality compared to adding an SUs. These findings underscore the potential cardiovascular benefits of DPP-4is and their role in improving patient outcomes.